Pemberian Madu Trigona Sp. (Kelulut) Dan Sari Jeruk Siam Sambas Terhadap Kadar Hemoglobin Darah (Hb) Ibu Hamil - Dahliansyah Dahliansyah; Yanuarti Petrika (Jurnal Surya Medika (JSM), 2020)
Anemia of pregnant women is at risk of increasing abnormal labor, the risk of maternal infection, and the tendency of bleeding which will have an impact on maternal and infant mortality. Bees (Trigona sp) are known to produce honey that contains vitamin C, functions as an antibiotic, antitoxin, antioxidants and to enhance the body's immune system, as well as the content of vitamin A, iron (Fe), and vitamin B12 which functions as the formation of red blood cells and hemoglobin prevents anemia. The purpose of this study was to analyze the effect of giving Trigona sp. Honey. (Kelulut) and Sambas Siam against the blood hemoglobin (Hb) levels of pregnant women. The Pre-Experiment Designs research method was using the Non-Randomized One Group Pretest-Postest Design, in which a group was given the treatment of Trigona sp Honey and Sambas siamas orange juice and then the results were observed, and the pretest and posttest were conducted. The subjects of this study were third-trimester pregnant women in the work area of the Karya Mulya Public Health Center. The sample in this study was 30 pregnant women. The sampling technique uses purposive sampling method, data analysis uses a paired t-test. The results showed that there was a significant influence in the administration of Trigona sp. Honey. (Kelulut) and Siam Sambas Oranges to increase blood hemoglobin (Hb) levels in pregnant women with Sig. (2-tailed) obtained 0,000 <0.005. Conclusion giving honey Trigona sp. (Kelulut) and Siam Sambas to pregnant women can increase blood hemoglobin (Hb) levels.